ND3$ extD^{3}$ QNet: Noisy dueling‐double‐deep q‐network for reconfigurable intelligent surfaces - Jihyung Kim; Junghyun Kim (Electronics Letters, 2024)
Abstract Low‐cost passive reconfigurable intelligent surfaces that provide coverage expansion in wireless communication networks are facing challenges in phase shift optimization due to limitations in acquiring channel information for sub‐channels. To overcome this, a new approach that improves both the convergence speed and overall performance relative to the existing state‐of‐the‐art scheme is proposed. Experimental results in an environment with a Rician factor of 20 showed a 9.3% increase in the average sum data rate, and the probability of the sum data rate exceeding the threshold of 10 increased by 30%.